2016
DOI: 10.1186/s12888-016-1115-z
|View full text |Cite
|
Sign up to set email alerts
|

Silybin supplementation during HCV therapy with pegylated interferon-α plus ribavirin reduces depression and anxiety and increases work ability

Abstract: BackgroundHepatitis C virus infection and interferon treatment are often associated with anxiety, depressive symptoms and poor health-related quality of life.To evaluate the Silybin-vitamin E-phospholipids complex effect on work ability and whether health related factors (anxiety and depression) were associated with work ability in subjects with chronic hepatitis C treated with Pegylated-Interferon-α2b (Peg–IFN) and Ribavirin (RBV).MethodsThirty-one patients (Group A) with chronic hepatitis and other 31 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…In another clinical study on these patients, they received PEGylated‐interferon alfa 2b and ribavirin and one supplement daily (contains 94‐mg silybin, vitamin E, and phospholipids) for 12 months. In this trial, no intense adverse effects were reported, although some symptoms such as weight loss, muscle pain, irritability, hyperglycemia, joint pain, and hypercholesterolemia were observed (Malaguarnera et al, ). As well as in another trial on these patients, 27 male and female patients (who were treated with ribavirin and interferon and still hepatitis C virus ribonucleic acids were detectable) received 20 mg/kg of intravenous silymarin for 14 or 21 days.…”
Section: Safety and Adverse Reactions Of Oral Silymarin In Humansmentioning
confidence: 75%
“…In another clinical study on these patients, they received PEGylated‐interferon alfa 2b and ribavirin and one supplement daily (contains 94‐mg silybin, vitamin E, and phospholipids) for 12 months. In this trial, no intense adverse effects were reported, although some symptoms such as weight loss, muscle pain, irritability, hyperglycemia, joint pain, and hypercholesterolemia were observed (Malaguarnera et al, ). As well as in another trial on these patients, 27 male and female patients (who were treated with ribavirin and interferon and still hepatitis C virus ribonucleic acids were detectable) received 20 mg/kg of intravenous silymarin for 14 or 21 days.…”
Section: Safety and Adverse Reactions Of Oral Silymarin In Humansmentioning
confidence: 75%
“…Lastly, the HCC risk factors in chronic HBV infection are different and the pathogenesis is characterized by the combined action of different alterations involving genetic, epigenetic and immunological factors [63][64][65][66][67][68][69][70][71] (Figure 1). …”
Section: Development Of Hcc In Chronic Hbv Infectionmentioning
confidence: 99%
“…In previous studies we observed that treatment with Peg-IFN and Ribavirin shows on increase in depression or irritable mood, in mental and physical fatigue severity, a decrease in attention, concentration and in memory activity [16,17]. The decrease of PWS in SVR and in ETR is associated with a reduction in both anxiety and depression status.…”
Section: Discussionmentioning
confidence: 83%
“…The impact of the HCV infection and antiviral therapy has been investigated in several studies [10,11,13,16,17]. Various endogenous inflammatory cytokines and exogenous cytokine-associated to depression and anxiety has been correlated with specific risk factors that may allow for potential preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation